Crimean-Congo Hemorrhagic Fever Virus, Greece - Papa, Anna (Centers for Disease Control and Prevention, 2014)
Seroprevalence of Crimean-Congo hemorrhagic fever virus (CCHFV) is high in some regions of Greece, but only 1 case of disease has been reported. We used 4 methods to test 118 serum samples that were positive for CCHFV IgG by commercial ELISA and confirmed the positive results. A nonpathogenic or low-pathogenicity strain may be circulating.